2022
DOI: 10.1111/jth.15874
|View full text |Cite
|
Sign up to set email alerts
|

Exclusively breastmilk‐fed preterm infants are at high risk of developing subclinical vitamin K deficiency despite intramuscular prophylaxis at birth

Abstract: Background: There is near-global consensus that all newborns be given parenteral vitamin K 1 (VK 1 ) at birth as prophylaxis against VK deficiency bleeding (VKDB).Breastmilk has a low VK content and cases of late VKDB are reported in exclusively breastmilk-fed preterm infants despite VK prophylaxis at birth. Objectives:To assess the prevalence of functional VK insufficiency in preterm infants based on elevated underγ-carboxylated (Glu) species of Gla proteins, factor II (PIVKA-II), and osteocalcin (GluOC), syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 80 publications
2
20
0
Order By: Relevance
“…These small concentrations and rapid tissue loss, lead directly to the discovery of VK in chicks, who are uniquely sensitive to the withdrawal of VK from the diet, showing clinical evidence of deficiency within hours. Similar vulnerabilities are seen in human infants, resulting in nearly universal worldwide parenteral administration of VK shortly after birth to prevent vitamin K deficiency bleeding (VKDB) of early infancy [231], which is sometimes associated with vision loss. Unique also to VK is the fact no known toxicity to naturally occurring VK isoforms have been shown, and natural forms of VK "appear to be essentially innocuous" [232].…”
Section: Discussionmentioning
confidence: 93%
“…These small concentrations and rapid tissue loss, lead directly to the discovery of VK in chicks, who are uniquely sensitive to the withdrawal of VK from the diet, showing clinical evidence of deficiency within hours. Similar vulnerabilities are seen in human infants, resulting in nearly universal worldwide parenteral administration of VK shortly after birth to prevent vitamin K deficiency bleeding (VKDB) of early infancy [231], which is sometimes associated with vision loss. Unique also to VK is the fact no known toxicity to naturally occurring VK isoforms have been shown, and natural forms of VK "appear to be essentially innocuous" [232].…”
Section: Discussionmentioning
confidence: 93%
“…12 Studies have shown evidence of subclinical VK deficiency in a considerable number of exclusively breastfed preterm infants at 2-5 months of age, which is related to the duration of breastfeeding. 13 There is a near-global consensus that VK prophylaxis should be provided to all newborn infants to prevent VKDB and its life-threatening consequences. 13 Various regimens of parenteral and oral prophylaxis have been implemented over the years.…”
Section: Introductionmentioning
confidence: 99%
“…13 There is a near-global consensus that VK prophylaxis should be provided to all newborn infants to prevent VKDB and its life-threatening consequences. 13 Various regimens of parenteral and oral prophylaxis have been implemented over the years. [14][15][16][17][18] Phylloquinone, the vitamin K1 (VK1), is the only form used therapeutically in humans, synthesized by plants and algae.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations